The Influence of Motorcyclistsâ Attitudes on Traffic Accidents and Offences - Wedagama, D. M. Priyantha (Jurnal Teknik Sipil, 2017)
AbstractThis study aims at identifying determinants of motorcyclistsâs attitudes and analysing their influences on theÂ occurrence of traffic accidents and offences. A self-reported questionnaire survey was distributed in year 2016Â among a representative sample of motorcyclists in Denpasar, Bali. The questionnaire consisted variables of socioeconomicÂ factors, the use of motorcycle and riding history, learning method and experience on riding motorcycles,Â motorcyclist attitudes and involvement in traffic accidents and offences. The results show that age and educationÂ level influenced learning method and experiences variables while gender did on motorcyclistsâ attitude. In addition,Â learning method and experience and motorcyclistsâ attitudes on the road were two significant factors respectivelyÂ that negatively affected motorcyclistsâ involvement in traffic accidents and offences. In other words, ages, educationÂ level and gender have significant indirect influences on motorcyclistsâ involvement in traffic accidents and offences.Â The influence of gender implies that compared to females, male motorcyclists are more likely to fail giving priorityÂ and violate parking signs. In comparison with females, male motorcyclists therefore, are more likely to get involvedÂ in traffic accidents and offences. Interestingly, this study indicated that motorcyclists with a higher education wereÂ not a guarantee not to involve in traffic accidents and offences.AbstrakPenelitian ini bertujuan untuk identifikasi faktor-faktor penentu sikap pengendara sepeda motor dan pengaruhnyaÂ terhadap terjadinya pelanggaran dan kecelakaan lalu lintas. Pengambilan data dilakukan pada tahun 2016 denganÂ menyebarkan kuesioner kepada pengendara sepeda motor di Denpasar, Bali. Kuesioner memuat variabel-variabelÂ sosial ekonomi, rekam penggunaan sepeda motor, teknik latihan dan pengalaman berkendara dengan sepedaÂ motor, sikap pengendara motor dan keterlibatan terkait pelanggaran dan kecelakaan lalu lintas. Hasil penelitianÂ menunjukkan bahwa usia dan tingkat pendidikan berpengaruh kepada teknik latihan dan pengalaman berkendaraÂ sementara jenis kelamin berpengaruh pada sikap pengendara sepeda motor. Teknik latihan dan berkendara danÂ sikap pengendara sepeda motor adalah dua faktor penting yang berdampak negatif terhadap keterlibatanÂ pengendara sepeda motor dalam pelanggaran dan kecelakaan lalu lintas. Usia, tingkat pendidikan dan jenisÂ kelamin memiliki pengaruh tidak langsung pada keterlibatan pengendara sepeda motor dalam pelanggaran danÂ kecelakaan lalu lintas. Pengendara sepeda motor pria, dibandingkan dengan wanita, mempunyai kemungkinanÂ untuk tidak memberikan prioritas kepada pengendara bermotor lainnya dan pelanggaran rambu lalu lintasÂ (parkir). Dengan perkataan lain, pengendara sepeda motor laki-laki di Denpasar, mempunyai kemungkinan terlibatÂ pelanggaran dan kecelakaan lalu lintas. Penelitian ini juga memperlihatkan bahwa pengendara sepeda motorÂ dengan pendidikan tinggi bukan jaminan tidak terlibat dalam pelanggaran dan kecelakaan lalu lintas.